Industrial path analysis for CO2 transfers induced by final consumption: A comparison of the United States and China. (1st April 2020) - Li, Yaoguang; Xu, Dongxiao; Wang, Jiawen; Zhang, Yan; Yu, Xiangyi
Abstract: The final consumption of the United States and China strongly affects global greenhouse gas emission. We analyzed the amount of CO2 transfers by the two countries caused by final consumption and its structural distribution from 1993 to 2013. We identified the key domestic and foreign sectors and transfer paths among the sectors that contributed most to final consumption. The total consumption-based transfer quantity increased to 1.2 and 3.6 times the 1993 value for the United States and China, respectively, whose domestic production and consumption were around 75 and 90% of the total, respectively. The key domestic sectors in both countries were the Electricity, Gas, and Water sector, the Transportation sector, and the Petroleum, Chemical, and Non-Metallic Mineral Products sector, which each accounted for 20–30% of the total. Among the domestic transfer paths, the American Electricity, Gas, and Water sector and Transportation sector, and China's Construction sector, had the most connections to other sectors. We identified frequent contributions of foreign sectors to final consumption in both countries. Their dominant transfers were to the American Public Administration sector and Education, Health, and Other Services sector, and to China's Construction sector. Understanding these key sectors and the paths among them can provide the scientific basis for improved national emission mitigation plans. Highlights: We focused on the CO2 transfer of the United States and China from 1993 to 2013. We decomposed the consumption-based CO2 in four structural parts. We presented industrial and path features domestically and abroad of these two countries.